Fourier method employed for solving thermoelastisity problems for rectangular plate with opening and inclusions - Sukhorolsky, M. A.; Kostenko, I. S.; Sorokaty, M. I.; Lubytska, O. Z. (Видавництво Львівської політехніки, 2012)
Dynamic problems of thermoelasticity for the rectangular plate with absolutely rigid inclusion and opening are considered. The problem is reduced to the system of boundary integral equations, numerical solution of which is constructed by the collocation method. Розглянуто динамічні задачі термопружності для прямокутної пластини з повністю жорсткими включеннями та відкриттям. Задача зводиться до системи граничних інтегральних рівнянь, чисельні розв’язання яких будуються за допомогою методу колокації.
Keywords: system of boundary integral equations; collocation method; система граничних інтегральних рівнянь; метод колокації